End of season influenza vaccine effectiveness in primary care in adults and children in the United Kingdom in 2018/19. Issue 3 (16th January 2020) - Pebody, Richard G.; Whitaker, Heather; Ellis, Joanna; Andrews, Nick; Marques, Diogo F.P.; Cottrell, Simon; Reynolds, Arlene J.; Gunson, Rory; Thompson, Catherine; Galiano, Monica; Lackenby, Angie; Robertson, Chris; et al.
Abstract: 2018/19 was the first season of introduction of a newly licensed adjuvanted influenza vaccine (aTIV) for adults aged 65 years and over and the sixth season in the roll-out of a childhood influenza vaccination programme with a quadrivalent live attenuated influenza vaccine (LAIV). The season saw mainly A(H1N1)pdm09 and latterly A(H3N2) circulation. End-of-season adjusted vaccine effectiveness (aVE) estimates against laboratory confirmed influenza infection in primary care were calculated using the test negative case control method adjusting for key confounders. End-of-season aVE was 44.3% (95% CI: 26.8, 57.7) against all laboratory-confirmed influenza; 45.7% (95% CI: 26.0, 60.1) against influenza A(H1N1)pdm09 and 35.1% (95% CI: −3.7, 59.3) against A(H3N2). Overall aVE was 49.9% (95%CI: −13.7, 77.9) for all those ≥ 65 years of age and 62.0% (95% CI: 3.4, 85.0) for those who received aTIV. Overall aVE for 2–17 year olds receiving LAIV was 48.6% (95% CI: −4.4, 74.7). The paper provides evidence of overall significant influenza VE in 2018/19, most notably against influenza A(H1N1)pdm09, however, as seen in 2017/18, there was reduced, non-significant VE against A(H3N2). aTIV provided significant protection for those 65 years of age and over.